Vendor maintenance or supplier management and reporting of shop management system (VMR) - Ng, Jit Huan (2010)
Some of the small clothing stores or boutique shops are using different system to running different business activities such as cashier machine to handle business transaction, manually record stock information and staff personal detail or even not recording the information at all. This application will provide features such as cashier to handle sales transaction, stock management to control stock availability, staff information management to handle employee details, supplier information management for purchasing order and generating report. For vendor maintenance or supplier information management, user shall register the vendor information into the system database. It can be to generate purchase order which can be print out used to order stock. User shall choose the stock from existing stock list or key in new kind of stock for place new purchase order. After selection, purchase order in standard format will be generated and printed out. For generating report function, this system can generate a report which contained the vendor information, stock information, daily, monthly and annual sales of the shop stored in the database.